Analysis of the Difficulties of Class VIII Students of Private Middle School PAB 1 Klumpang in Solving Story Problems Arithmetic Sequences and Series - Al Qadar, Mustapa; Firdaus, Muliawan (Lembaga Riset Mutiara Akbar, 2023)
Word problems are specific problems that require good reading skills to solve and are one of the requirements to be able to understand the main content of the problem. The subject of mathematics that students find difficult is the subject of arithmetic sequences and series. This research is qualitative research. This study aims: (1) To find out what causes students' difficulties in solving word problems. (2) To find out what percentage of students' difficulties in solving word problems. The sample for this study was students of class VIII-1 at Private Middle School PAB 1 Klumpang for the 2022/2023 academic year, which consisted of 34 students. Data were obtained by means of story questions and interviews. Based on the results of the analysis carried out, students who experienced difficulties in working on the story problem tests included, namely, students' difficulties in converting story questions into mathematical form (18%), students' difficulties in finding out what formula to use in solving word problems (31 %), and students' difficulties in completing arithmetic operations when solving word problems (37%). In addition, there are also other factors that cause student difficulties, namely being in a hurry to answer questions, not being ready to take the test, not understanding the meaning of the questions, and not mastering the concepts related to the questions